Le racisme environnemental, avec Vanessa Destiné - Destiné, Vanessa; Radio-Canada, Médias numériques de (2022)
La journaliste Vanessa Destiné explique ce qu’est le racisme environnemental et comment on peut le combattre. Face à la crise climatique, on n’est pas tous égaux et ce n’est pas par hasard. 💰 Au Canada et à l’étranger, un nombre disproportionné de personnes autochtones et racisées sont touchées par des questions environnementales. 🚱 Dans cet épisode de l’ABC, la journaliste Vanessa Destiné explique ce qu'est le racisme environnemental et comment on peut le combattre. 💪🏾💪🏻💪🏿 On souhaite remercier Lourdenie Jean de l'organisme « L'environnement c'est intersectionnel ».
Keywords: approches et analyses; cours; environnement; inégalités; pol5480; premier cycle; pédagogie; racisme; systèmes d'oppressions; thématiques; écoféminisme

La vulnérabilité face aux changements climatiques - Gagnon-Bouchard, Laurie (Spirale, 2022)
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; cours; environnement; fem3600; premier cycle; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; écoféminisme

Ville féministe : notes de terrain - Kern, Leslie (Les éditions du remue-ménage, 2022)
À qui appartient la ville? Sûrement pas aux femmes. Souvent le théâtre des violences ordinaires ou frontales, la ville repose sur des fondations sexistes. Kern s'attarde à la manière dont les relations de genre, de classe, de race, d'âge se déploient dans la ville. Elle nous invite à redéfinir et à nous réapproprier les espaces urbains. Comment rendre nos villes plus féministes? Partant de son expérience quotidienne de citadine à différentes époques de sa vie (enfant, adolescente, étudiante, travailleuse, militante et mère), elle s'appuie sur les théories d'urbanisme, des travaux de géographes féministes et des références à la culture pop pour montrer comment une ville genrée qui s'embourgeoise exclut les populations marginalisées, mais également pour évoquer les possibles configurations d'une ville plus inclusive.
Keywords: approches et analyses; cours; design; discipline; environnement; fem1250; inégalités; premier cycle; racisme; ressource en ligne; sexisme; systèmes d'oppressions; thématiques; urbanisation; urbanisme; violences

Gender, climate breakdown and resistance: The future of human rights in the shadow of authoritarianism - Rosamond, Annika B.; Davitti, Daria (Nordic Journal of Human Rights, 2022)
In this article we examine the future of human rights by looking at how ‘authoritarianism’, in its multifaceted forms and manifestations, intersects with existing discourses on climate change, environmental protection, populism and ‘gender deviance’. By adopting an intersectional lens, we interrogate the emergence of the right to a healthy environment and reflect on whether it will help against the double challenge faced by human rights: of climate breakdown and rising authoritarianism. We study the link between authoritarianism and populism, focusing on far-right populism and the creeping authoritarian features that we can associate with far-right groups, both movements and parties. We also consider how certain understandings of nature and the environment are put forward by authoritarian regimes. This leads us to consider so-called ‘ecologism’ and the ways in which far-right movements draw upon green thought on the natural environment to further a gendered agenda based on conceptions of nature as a ‘national treasure’. These conceptions, as we demonstrate, go hand in hand with policies that promote national identity and directly undermine the rights of migrants, ethnic minorities, women and LGBT+ groups. © 2022 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; LGBTQIA2+; approches et analyses; capitalisme; changements climatiques; discipline; droits des femmes*; droits humains; environnement; histoire et politique; intersectionnalité; patriarcat; populisme de droite; projet charge mentale; périodes historiques; racisme; science politique; science politique et droit; sexisme; systèmes d'oppressions; thématiques; écologisme d'extrême-droite

Systems thinking in COVID-19 recovery is urgently needed to deliver sustainable development for women and girls - Omukuti, Jessica; Barlow, Matt; Giraudo, Maria Eugenia; Lines, Tallulah; Grugel, Jean (The Lancet Planetary Health, 2021)
In low-income and middle-income countries, such as those in sub-Saharan Africa and Latin America, the COVID-19 pandemic has had substantial implications for women’s wellbeing. Policy responses to the COVID-19 pandemic have highlighted the gendered aspect of pandemics; however, addressing the gendered implications of the COVID-19 pandemic comprehensively and effectively requires a planetary health perspective that embraces systems thinking to inequalities. This Viewpoint is based on collective reflections from research done by the authors on COVID-19 responses by international and regional organisations, and national governments, in Latin America and sub-Saharan Africa between June, 2020, and June, 2021. A range of international and regional actors have made important policy recommendations to address the gendered implications of the COVID-19 pandemic on women’s health and wellbeing since the start of the pandemic. However, national-level policy responses to the COVID-19 pandemic have been partial and inconsistent with regards to gender in both sub-Saharan Africa and Latin America, largely failing to recognise the multiple drivers of gendered health inequalities. This Viewpoint proposes that addressing the effects of the COVID-19 pandemic on women in low-income and middle-income countries should adopt a systems thinking approach and be informed by the question of who is affected as opposed to who is infected. In adopting the systems thinking approach, responses will be more able to recognise and address the direct gendered effects of the pandemic and those that emerge indirectly through a combination of long-standing structural inequalities and gendered responses to the pandemic.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afrique; afrique subsaharienne; amérique latine; amériques; approches et analyses; environnement; justice climatique; justice sociale; pandémie; patriarcat; politiques publiques; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé publique; sexisme; systèmes d'oppressions; thématiques

Surviving the grind: how young black women negotiate physical and emotional labor in urban space - McCurn, Alexis S. (Sociological Spectrum, 2020)
This study draws on nearly 2 years of field research in Central East Oakland, CA, to provide an ethnographic account of the daily experiences of poor, young, black women in urban space. Few scholars have explored the collective experiences of young women living in the inner-city and the innovative strategies they develop to navigate daily life in this setting. The accounts from young women in this study reveal the different types of formal and informal labor black women do to ensure survival in the inner-city and how they describe this daily work as the “grind.” The intersection of formal and informal labor that makes up the grind is reflected in three dimensions: the half-time hustle, underground entrepreneurship, and informal support networks. Like men in the neighborhood women must contend with underemployment, poverty and race and class isolation. I explain how black women are impacted in very specific ways by these key structural shifts and harsh structural conditions and must in turn manage constraining and contradictory gendered expectations while negotiating the grind. © 2020, © 2020 Taylor & Francis Group, LLC.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; capitalisme; environnement; intersectionnalité; milieu urbain; projet charge mentale; périodes historiques; racisme; régions géographiques; sexisme; stratégie de survie; systèmes d'oppressions; thématiques; travail; états-unis